Legal access to our musical history: an investigation into the copyright implications of archived musical recordings held at the International Library of African Music (ILAM) in South Africa - McConnachie, Boudina Elizabeth (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 2009)
This thesis explores the South African Copyright Act No. 98 of 1978 as it pertains to the archived holdings at the International Library of African Music (ILAM) situated at Rhodes University, Grahamstown, South Africa. The purpose of analysing this law is to advise and assist ILAM in fulfilling royalty payment obligations as stipulated in a contract signed between ILAM and the Smithsonian Global Sound (formally Global Sound Network) in 2001. In order to clearly comprehend the scope of the royalty payment clause in the Smithsonian Institution's contract with ILAM, this research includes an examination of: the history and nature of South African copyright as a sub-structure of intellectual property; specific internationally documented copyright infringement cases; the recording and documentation practices of Hugh Tracey (ILAM's founder and director from 1954 to 1977); the contract between Global Sound Network and ILAM; and contentious issues surrounding collective ownership and indigenous knowledge. In conclusion, this research suggests equitable solutions to ILAM's copyright concerns and proposes the Eastern Cape Music Archiving Project (ECMAP) as a practical vehicle to assist the South African Department of Trade and Industry in implementation of the South African Intellectual Property Amendment Bill (2008) if, and when, it is passed.
Keywords: Tracey, Hugh; International Library of African Music; South Africa. Copyright Act, 1978; Copyright Music -- South Africa; Music History and criticism